Studies and Antibacterial Activity of 2-Amino-4-(2’-Hydroxy-5’-Methyl-4’,6’-Dibromophen-1’-yl)-6-Substituted Phenyl Pyrimidine Derivatives - Naik, S.M.; Naik, H.B. (Asian Journal of Chemistry, 2010)
The reaction of 2' -hydroxy-5' -methyl-4' ,6' -dibromochalcones with alcoholic solution of guanidine nitrate and aqueous sodium hydroxide solution gave the corresponding 2-amino-4-(2'hydroxy- 5' -methyl-4',6' -dibromophen-1' -yl)-6-substituted phenyl pyrimidine derivatives. The structure of these compounds has been studied by elemental analysis and spectral method. The antibacterial activity of these compounds has also been investigated.